2013
DOI: 10.1172/jci66241
|View full text |Cite
|
Sign up to set email alerts
|

Balancing GRK2 and EPAC1 levels prevents and relieves chronic pain

Abstract: Chronic pain is a major clinical problem, yet the mechanisms underlying the transition from acute to chronic pain remain poorly understood. In mice, reduced expression of GPCR kinase 2 (GRK2) in nociceptors promotes cAMP signaling to the guanine nucleotide exchange factor EPAC1 and prolongs the PGE 2 -induced increase in pain sensitivity (hyperalgesia). Here we hypothesized that reduction of GRK2 or increased EPAC1 in dorsal root ganglion (DRG) neurons would promote the transition to chronic pain. We used 2 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
119
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(126 citation statements)
references
References 71 publications
7
119
0
Order By: Relevance
“…Earlier studies by us and others have shown that Epac1 protein levels in the DRG are increased in the CFA model of chronic inflammatory pain, whereas GRK2 levels are decreased (16,17,(30)(31)(32). In addition, we presented evidence that Epac1-dependent pain signaling is inhibited by GRK2, but the mechanism remained to be determined (17).…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…Earlier studies by us and others have shown that Epac1 protein levels in the DRG are increased in the CFA model of chronic inflammatory pain, whereas GRK2 levels are decreased (16,17,(30)(31)(32). In addition, we presented evidence that Epac1-dependent pain signaling is inhibited by GRK2, but the mechanism remained to be determined (17).…”
Section: Discussionmentioning
confidence: 49%
“…In addition, we presented evidence that Epac1-dependent pain signaling is inhibited by GRK2, but the mechanism remained to be determined (17). Here, we identify GRK2, to our knowledge, as the first kinase known to directly phosphorylate Epac1, identify the site of phosphorylation, and demonstrate that this phosphorylation event inhibits Epac1-to-Rap1 signaling.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…GRK2 heterozygous mice suffer from chronic hyperalgesia due to continued microglial activation via p38-dependent TNFα production (Eijkelkamp, Heijnen, et al, 2010; Willemen et al, 2010) and prolonged activation of prostaglandin E2-mediated pathway. This prolonged activation is mediated through interactions with EPAC1 (exchange protein directly activated cAMP) and activation of protein kinase Cε- and ERK-dependent pathways (Eijkelkamp, Wang, et al, 2010; H. Wang et al, 2013).…”
Section: Grks In Inflammatory Signaling and Diseasementioning
confidence: 99%